MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SD NEGERI BAHAL PADANGLAWAS UTARA - Mulkan Hasibuan (PIONIR: JURNAL PENDIDIKAN, 2021)
This research was conducted to get an overview of the management of Islamic religious education learning at SD Negeri Bahal Padanglawas Utara. The research approach that is more appropriate to use is the qualitative approach that the reason why researchers choose the qualitative approach method has a natural background as a data source. The results of this study are PAI learning plans which include details of Effective Week, Annual Program, Semester Program, Minimum Completeness Criteria (KKM), SK and KD Mapping, Competency Standards and Basic Competencies, Syllabus, RPP. Implementation of face-to-face and non-face-to-face learning (learning experience). Face-to-face activities at SD Negeri Bahal Padanglawas Utara are carried out by developing direct interactions between teachers and students such as using lecture, discussion, assignment and question and answer (quiz) methods. Learning supervision is always carried out on students if they want to better understand learning, especially in doing assignments and also in learning discussions, observations. The learning evaluation used in the competency-based assessment system is a form of free test, usually this is done before the lesson starts in approximately 15 minutes. Oral questions by asking questions briefly and firmly then selecting students at random to answer the daily test, carried out after finishing one subject.